2010
DOI: 10.1021/la103615b
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Protein-Based Nanoparticles Induce Lipid Bilayer Disruption: Carbon Nanotube Conjugates and Amyloid Fibrils

Abstract: Along with recent progress of nanotechnology, concern has risen about biological impacts of nanoparticles deriving from their interaction with cell membranes. Nanoparticles tend to adsorb proteins in vivo. Therefore, the physical properties of the conjugates to cell membranes must be investigated to elucidate and assess their properties. We examined whether one-dimensional protein-based nanoparticles induce liposome leakage in physiological saline. Carbon nanotube conjugates with adsorbed lysozyme interacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…77 Electrostatic interactions can also occur between protein-coated CNTs and liposomes, leading to liposome leakage. 78 Surface charged polystyrene nanoparticles bind to liposomes and induce surface reconstruction of the phospholipid membranes, indicating a potential structural perturbation of the cellular membrane by nanoparticles (Figure 3). 73 Nanoparticle-induced lipid bilayer rearrangements are limited to bubble-like liposomes, not supported bilayers.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…77 Electrostatic interactions can also occur between protein-coated CNTs and liposomes, leading to liposome leakage. 78 Surface charged polystyrene nanoparticles bind to liposomes and induce surface reconstruction of the phospholipid membranes, indicating a potential structural perturbation of the cellular membrane by nanoparticles (Figure 3). 73 Nanoparticle-induced lipid bilayer rearrangements are limited to bubble-like liposomes, not supported bilayers.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…22 Since the PC affects the properties of the NP surface, it has significant impact on the interaction between membrane and NPs. [23][24][25][26][27] Many studies are described in the literature where NP cellular uptake is related to the presence of a PC on the NPs in biological fluids, [28][29][30] in particular it has been shown that a key factor in NPs cellular uptake is their adhesion to the cell membrane that significantly affects their final uptake rates. 31 NP-cell membrane interaction is a complex dynamic process in which the environmental proteins are known to play an important multifaceted role: not only they adsorb onto the NP surface forming the PC, but also they compete with the NP in the interaction with the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…S-amyloid is generated from HEWL incubated under acidic conditions (pH 2) with saline under continuous agitation by a stirrer, as reported previously (Hirano et al, 2010;Takai et al, 2014c). Under this condition, amyloid fibrils are mainly formed from nonfragmented monomers of HEWL without hydrolysis.…”
Section: Preparation Of Amyloid Fibril From Selfassembled Lysozyme (Smentioning
confidence: 53%